Abordagem das causas e consequências da gravidez não planejada no ensino de ciências - Furtado, Edmarcia Aparecida Esposito (2015)
There is an increase in the number of adolescents who initiate their sexual life before they reach the age of 16, putting their physical integrity at risk, as well as the risk of contracting a Sexually Transmitted Disease (STD) or an unwanted pregnancy. An unwanted pregnancy in adolescence brings consequences for health, education and can become an obstacle to the development of its full potential. Therefore, it is necessary for Science Education in schools to deal more objectively with contents related to sexual intercourse, such as pregnancy and sexually transmitted diseases (STDs), which are inserted in the National Curriculum Parameters (NCP). That the information reaches adolescents correctly without the misunderstandings caused by popular beliefs. The objective of this study was to verify the level of information that adolescents have regarding pregnancy and Sexually Transmitted Diseases. The method used for the data collection was the application of a questionnaire for adolescents aged 10 to 17 years old, at the State School "Marechal Cândido Rondon" located in the city of Itapevi, São Paulo. The realization of the present research allowed a reflection on a dilemma in the life of the adolescents and places the school in front of great challenges, that is to guide the young adolescents on the dangers of the early sexual initiation, to prevent the pregnancy and the risks of an illness Sexually transmitted diseases and combating school dropout due to pregnancy. It should be taken into consideration that adolescence is a phase of life characterized by physical, psychological and social changes and by the discovery of sexuality. Taking all this into account, we realize that the school plays a fundamental role in the dissemination of information in a correct and adequate way considering the reality of these adolescents, because as we have already observed parents can not always follow the children's lives, Of a theme so complex and wrapped in taboos. Thus, the role of the teacher is also fundamental as a sexual educator. For many students, this professional is the only person they can count on to broaden their knowledge about sexuality and develop a new view of facts that, sometimes in their social environment, can be treated as unimportant to their lives, as is Case of the "first time" decision or teenage pregnancy. An educator who is aware of the importance of this role makes all the difference in the lives of these adolescents, becoming a person capable of increasing the baggage of this teenager's life.